STATUS GIZI IBU SAAT HAMIL, BERAT BADAN BAYI LAHIR DAN PEMBERIAN ASI EKSKLUSIF TERHADAP KEJADIAN STUNTING - Dadang Rosmana; Rita Yuliani; Gurid PE Mulyo; Roro Nur Fauziyah; Agustina Indri Hapsari (Jurnal Gizi dan Dietetik, 2022)
Stunting is a condition where height or body length is less than age. The causes of stunting are maternal nutritional status during pregnancy, low birth weight and exclusive breastmilk. The prevalence of stunting in Sumedang regency in 2020 is 12.51%. The purpose of this study was to determine the relationship between the maternal nutritional status during pregnancy, birth weight and exclusive breastmilk with stunting in Puskesmas Jatinunggal, Sumedang. The type of research is analysis observation with cross sectional with a sample of 64 toddler, purposive sampling as the sampling technique. The type of data used is secondary data as maternal nutritional status during pregnancy, birth weight, exclusive breastmilk, height for age. The results showed 25 toddlers were stunted (39.1%), 18 mothers during pregnancy who experienced chronic energy deficiency (28.1%),15 toddlers who experienced LBW (23.4%), not exclusive breastfeeding 24 toddlers (37.5%). Bivariate results there was no relationship between nutritional status during pregnancy and the incidence of stunting (p 0.528). There is a relationship between birth weight and the incidence of stunting (p 0.00). There is a relationship between exclusive breastfeeding and the incidence of stunting (p 0.00). The most influential variable on the incidence of stunting is the birth weight of the baby. LBW provides 21,330 opportunities to cause stunting.